The Influence Of Friction Stir Welding Parameters On Mechanical Properties Of 6061-T6 Aluminum Alloy - Mohsin Hameed, Atiyah (2016)
Aluminum alloy 6061 is frequently utilized for construction of aircraft structures, such as aerostructures and wings, which is the most common in home built aircraft than commercial or military aircraft. It is generally present low weldability by conventional fusion welding process. The advancement of Friction Stir Welding (FSW) has provided an alternative improved means of suitably producing weld joint of AA6061-T6. Unlike in conventional fusion welding, friction stir welds will not confront troubles like distortion, porosity and cracking, and welds are produced with good surface finish. The welding parameters rotational speed and welding speed play a key role in determining the joint characteristics. This experimental study presents the effect of welding parameters (rotational speed and welding speed) on hardness, tensile strength, bending strength and microstructure of 6061-T6 aluminum alloy joints produced by FSW. In this study, FSW is performed using CNC vertical milling machine with three different welding speeds of (50, 100, 150 mm/min) and three different tool rotation speeds of (800, 1000, 1200 rpm). Tool made of steel (H13) consisting of 12 mm diameter shoulder and 4 mm diameter pin with an overall height of 2.8 mm making it little shorter than the plate thickness (3mm). The outcomes refer that the best tensile strength of FSW joints is 163 MPa and joint efficiency is 72% which were welded with welding parameters of (1200 rpm and 50 mm/min). It was observed that the tensile strength, joint efficiency, hardness, and bending strength of the weldments increased with increasing the tool rotation speed and decreasing travel speed. The microstructure of the welded specimens has been studied by using optical microscopy. The formation of fine equiaxed grains and very fine strengthening precipitates (Mg₂Si) in the stir or weld region are the reasons for higher tensile strength, bending strength and hardness of FSW joints.